2023
DOI: 10.1021/acsami.2c21884
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium-Tailored Silicon Composite with Furthered Ion Diffusion Behaviors for Longevity Lithium-Ion Storage

Abstract: As one of the promising anode materials, silicon has attracted much attention due to its high theoretical specific capacity (∼3579 mAh g–1) and suitable lithium alloying voltage (0.1–0.4 V). Nevertheless, the enormous volume expansion (∼300%) in the process of lithium alloying has a great negative effect on its cyclic stability, which seriously restricts the large-scale industrial preparation of silicon anodes. Herein, we design a facile synthesis strategy combining vanadium doping and carbon coating to prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…As a semiconductor, both the intrinsic electronic conductivity and the ionic conductivity of Si are not sufficient. [ 96 ] For the thin film Si anode, the side effect of such insufficient ionic/electronic conductivity is acceptable, while for the sheet‐type Si anodes, this drawback must be conquered. Accordingly, the introduction of other components that can deliver high ionic conductivity or electronic conductivity in anodes is necessary for the design of Si‐SSBs.…”
Section: Inorganic (Sulfides) Sse‐based Si‐ssbsmentioning
confidence: 99%
“…As a semiconductor, both the intrinsic electronic conductivity and the ionic conductivity of Si are not sufficient. [ 96 ] For the thin film Si anode, the side effect of such insufficient ionic/electronic conductivity is acceptable, while for the sheet‐type Si anodes, this drawback must be conquered. Accordingly, the introduction of other components that can deliver high ionic conductivity or electronic conductivity in anodes is necessary for the design of Si‐SSBs.…”
Section: Inorganic (Sulfides) Sse‐based Si‐ssbsmentioning
confidence: 99%
“…These approaches can be viewed from a microscopic and mesoscopic perspective. [38] Copyright 2023, American Chemical Society. b) Ge.…”
Section: Si Materials (Microscopic and Mesoscopic Scale)mentioning
confidence: 99%
“…Doping with alien ions has been demonstrated as an effective strategy to improve the electronic conductivity and Li + ion diffusion coefficient of intercalation-type electrode materials. [13][14][15][16][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] For instance, Lu's group successfully introduced Ru 4+ into micron-sized TiNb 2 O 7 powders through a solid-state reaction and the Ru 0.01 Ti 0.99 Nb 2 O 7 exhibited better cycling and rate properties than pure TiNb 2 O 7 . 15 Sun et al reported an interstitial and substitutional V 5+ -doped TiNb 2 O 7 microspheres with enhanced electronic conductivity and ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%